Pengaruh model pembelajaran kooperatif tipe jigsaw terhadap kemampuan menganalisis dalam pembelajaran sejarah indonesia kelas XI SMAN 7 kerinci - Leni Karlina; Zafri Zafri (Jurnal Kronologi, 2021)
This research is motivated by the low ability to analyze students on Indonesian history learning materials, especially in the ability to analyze, one way to overcome these problems is to use the jigsaw type cooperative learning model. The purpose of this study was to examine the effect of the jigsaw type of cooperative learning model on the ability to analyze in learning Indonesian history. This type of research is a quantitative quasi-experimental type of research, the sample used is class XI IPS 3 as the experimental class and class XI IPS 4 as the control class. Data obtained by means of pretest and posttest using 40 objective questions. The average value of the pretest results for class XI IPS 3 is 11.31 while the class XI IPS 4 is 11.38. The average value of the post test results for class XI IPS 3 is 15.50 while class XI IPS 4 is 12.06. Furthermore, the data were analyzed by t test with SPSS version 23 program with sig value. (2-tailed) of 0.029 < (smaller) than 0.05, it means that HI is accepted and HO is rejected, saying that there are differences in students' analytical abilities in learning. Keywords: History Learning, Jigsaw Model, Analyzing Ability